2018
DOI: 10.1016/j.imlet.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

TLR8 combined withTLR3 or TLR4 agonists enhances DC-NK driven effector Tc1 cells

Abstract: Our data indicate that if in need of an enhanced DC-NK mediated cellular immunity one may select TLR agonists with defined synergistic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Furthermore, we observed a transient decrease in circulating NK cells subsets (CD56 dim ) following Poly-ICLC treatment, which may possibly reflect trafficking of this subset of NK cells to the tissues. In preclinical studies, Poly-ICLC has been shown to secondarily activate NK cells to enhance their cytotoxicity which may in turn augment the killing and elimination of latently infected cells alone (25, 55) or in combination with other TLR ligands (56).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed a transient decrease in circulating NK cells subsets (CD56 dim ) following Poly-ICLC treatment, which may possibly reflect trafficking of this subset of NK cells to the tissues. In preclinical studies, Poly-ICLC has been shown to secondarily activate NK cells to enhance their cytotoxicity which may in turn augment the killing and elimination of latently infected cells alone (25, 55) or in combination with other TLR ligands (56).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DC adjuvants are also key to induce DC maturation and activation and, thus, intensify the immune response. Various combinations of cytokines, TLR agonists, and CD40 ligands have been utilized with different DC vaccines [4, 9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that a co-stimulation of at least two TLRs is needed to build a robust IL12p70 induction. Similarly, significantly enhanced DC maturation and IFNγ production of NK cells has been found after co-stimulation with TLR8 and either TLR3 or -4 [67]. Using Poly(I:C)-encapsulating nanoparticles as a TLR3 agonist after BCG infection or specific TLR2 activation led to synergistic production of nitric oxide (NO) in mural BMDM [68].…”
Section: Synergy Of Different Prrsmentioning
confidence: 95%